Website-Based Information System Planning of Financial Archive in Medical Faculty of Universitas Sebelas Maret Surakarta: Perancangan Sistem Informasi Arsip Keuangan Berbasis Website pada Fakultas Kedokteran Universitas Sebelas Maret Surakarta - Puspitasari, Cahyani; Hastomo, Mursid Dwi; Pantjarani, Ari (RADIANT: Journal of Applied, Social, and Education Studies, 2022)
The website-based information system planning of archive and financial documentation in Medical Faculty of Universitas Sebelas Maret Surakarta (UNS) is provided from daily observation by the author as the administration and finance documentation staff there. Sub-division of administration and financial documentation has tight relation with the recording of financial inflows in the faculty. The frequent problem is the absence of detail recording of archive transfer (incoming and outgoing archives) so that archive loss often occurs because of untracked position or last holder of archive. Surely, it affects the process of administration to be more difficult and spends longer time. Unprepared archive monitoring makes difficulty in the searching when the staff is not in the place. Based on the background above, the problem discussed in this research is how to plan website-based information system planning of archive and financial documentation Medical Faculty of UNS. The goal of this research is to make information system in order to solve the happening problem and hindering the daily activities in the finance division of the faculty. The limitation of this research is more focused on the process of incoming and outgoing archives (archive transfer), saving archive from damage and lost, then processing and monitoring speed of the most updated archive condition. The method used in this information system planning is by using System Development Life Cycle (SDLC) with Waterfall model, using PHP programming language and MySQL database. The conclusion of this research is to make solutions to solve problems that are often faced by faculty in daily activities so as to create a better effective and more efficient work atmosphere, especially in setting up the storage and rescue of financial archives which is very important to store and need in the future.